THE IMPLEMENTATION OF FULL DAY SCHOOL AT SENIOR HIGH SCHOOL IN BULELENG REGENCY YEAR 2019/2020 - Prasetya, G. H.; Nitiasih, P. K.; Budiarta, L. G. R. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This study aimed to 1) investigate students’ perception on the implementation of the full day school in SMAN 1 Singaraja and SMAN 4 Singaraja 2) investigate teachers’ perception on the implementation of the full day school in SMAN 1 Singaraja and SMAN 4 Singaraja 3) investigate strength and weakness on the implementation of the full day school in SMAN 1 Singaraja and SMAN 4 Singaraja. The design used in this study was descriptive qualitative. The subjects of this study were 11th-grade students and teachers from SMAN 1 Singaraja and SMAN 4 Singaraja. The result showed that 1) the students’ perception on the implementation of Full Day School in SMAN 4 Singaraja and SMAN 1 Singaraja are categorized as positive. 2) the teachers’ perception on the implementation of Full Day School in SMAN 4 Singaraja and SMAN 1 Singaraja are categorized as positive. 3) the strengths of the full-day school were developing teacher’s creativity in terms of teaching and developing students’ creativity in terms of affective, cognitive and psychomotor 4) The weakness the students could be bored because of additional hours of learning Keywords: Advantages and disadvantages, Full day school, Teachers’ perception, Students’ perception